Study on stripping phase conditions on the levulinic acid extraction using supported liquid membrane - V., Rajendaran; S. M., Saufi; M. A. K., Zahari; A. W., Mohammad (Penerbit UMP, 2019)
Supported liquid membrane (SLM) is the most effective technique to extract and recover the desired product from the biomass products in a single step. The study of the operation parameters in SLM system is very important to improve the yield of extraction and recovery of the product. In this study, different types of stripping agents such as sodium hydroxide (NaOH), sodium carbonate, hydrochloric acid, trimethylamine, and water were tested in the SLM system to extract levulinic acid (LA). By using 0.3 M trioctylamine in 2-ethyl-1-hexanol as liquid membrane phase, it was found that NaOH was the best stripping agent to extract LA. The concentration of the NaOH stripping agent was varied from 0.25 M to 1 M. The best stripping agent concentration was 0.5 M, which gave an LA extraction of 86% from a 10 g/L LA aqueous solution. The flow rate of the feed and stripping phase was investigated from 25 mL/min to 125 mL/min. SLM operated at 75 L/min was found to be adequate in reducing the boundary layer thickness at both sides of the SLM phases without any leakage of the liquid membrane and breakage of the matrix support. At the best stripping condition, 89% of the LA was extracted using 0.5 M NaOH that operated at flow rate of 75 mL/min.